Challenges and Risks of Global Crisis in the European Labour Market - Georgeta Dragomir (EIRP Proceedings, 2012)
The world enters in the year 2012 facing a stark reality, one in three workers in the labor forceis currently either unemployed or poor. According Eurostat, 24.325 million men and women in the EU-27, of whom 16.925 million were in the euro area EA-17, were unemployed in January 2012. These datareflect acute problems in labor markets, in part created by the financial crisis and, if labor conditionsremain unfavorable for a long period, these problems could transform into another chronic problem. Thispaper takes, according to the statistical database, a comparative perspective on the labor market impact ofthe actual global crisis on Romania and European area. It starts from the reality that global crisis had asignificant impact on the development of unemployment in Europe countries, the rise in unemployment,being in relation to GDP reductions, varies. In this reality, only economic and social policies are fair,consistent, well-focused, efficient, which can reduce risks and keep a balanced budget and social order.